Digital Marketing Strategies to Enhance the Tourism Appeal of Pasir Panjang Beach, Pu’ungkeu Village Through a Blue Economy Framework - Isra Iradat, Muhammad; Alwi, Miftahul Jannah; Nunu, Arson Abd, Rasyid; Daud, Salma; Pitaan, Zulkifli (Universitas Muhammadiyah Palu, 2026)
Pasir Panjang Beach, located in Pu’ungkeu Village, Bungku Pesisir District, Morowali, Central Sulawesi, is a coastal destination characterized by a long stretch of white sand, clear seawater, and a tranquil marine atmosphere. These natural qualities make it an increasingly preferred leisure site among local visitors, particularly during weekends. However, limited digital exposure and promotional initiatives have hindered its wider recognition. This study aims to formulate digital marketing strategies to strengthen the branding of Pasir Panjang Beach as a sustainable marine tourism destination grounded in the blue-economy concept. A descriptive qualitative approach was applied through field observation, visual documentation, and literature review related to ecotourism and digital promotion. Findings indicate that digital content focused on natural beauty, sustainability narratives, and local community participation can significantly enhance destination visibility while fostering environmental preservation. Recommended strategies include creative content development, social media optimization, collaborative promotion, and applying green-tourism principles to reinforce the beach’s identity as an eco-friendly coastal tourism destination.